Pengembangan Buku Digital Interaktif pada Mata Pelajaran Matematika SMK - Nuryakin, Mokhamad; Marsono, Marsono; Prasetya, Didik Dwi (Universitas Nahdlatul Ulama Blitar, 2024)
The industrial revolution is currently developing very rapidly and has an impact on all lines of life, including the world of education. Digitalization of education needs to be carried out in order to keep up with world developments. Based on the results of observations, data was obtained that SMK Islam 1 Blitar only has 1 textbook title to support the implementation of the teaching and learning process for students and teachers in mathematics subjects using the independent curriculum. The textbooks owned are said to be available in the form of printed books so they require a large enough storage space. Therefore, it is necessary to develop media in the form of interactive digital books to improve student learning outcomes. The type of research and development used is the R&D model of the ADDIE. Data collection uses questionnaires and written tests. The validation results by all research subjects were declared valid with details of obtaining scores of 91% of material experts, 88% of media experts, 94% of teacher users, and student users in small groups 92%. Based on the results of the feasibility test carried out, an average percentage score of 87% was included in the eligibility criteria. In addition, the product developed was also declared effective for use with an achievement score of 87%.